(untitled) (Journal of the College of Basic Education, 2022)
The current research aims to identify (adventure) among middle school students (third intermediate grade) adolescents, and its relationship to (cognitive consistency) and (behavior control), and the correlation between the three variables, and the extent to which the variables (cognitive consistency) and (behavior control) contribute In the total change of the (adventure) variable.The research sample consisted of (412) students from (the third intermediate grade) in the Directorate of Education of Baghdad / Rusafa the third, and the measures (adventure, cognitive consistency, and behavioral control) were applied, and by using the correlation coefficient (Pearson) and (the t-test). ) and (multiple regression analysis), the results showed:1. There is a positive, statistically significant correlation between the three research variables.2. The variable (cognitive consistency) contributes to (5.1%) of the total variation of the variable (adventure).